PASSWORD BASED CIRCUIT BREAKER (International Journal of Food and Nutritional Sciences, 2022)
This project introduces an innovative password based circuit breaker for electric line man safety system makes use of a new concept of password. It is found that fatal electrical accidents to the line man are increasing during the electric line repair due to the lack of communication and co-ordination between the maintenance staff and the electric substation staff. Hence to avoid this we are implementing a password based circuit breaker. These passwords provide total control to the system to turn on or off the supply to each line. The maintenance staff e.g. line man has the control to turn ON/OFF the line. If there is a problem in any particular section of the supply line, then staff wants to turn off that line and repair it. For that the using a matrix keypad he can enter it in the system. Then the system compares the entered password with the generated password. If the pass words are matched, then the supply to that line will be made OFF. Now he can repair the line more safely and after it is over he can turn on that line by using the password. This ensures security of the worker because no one can turn on the line without his permission.